Micro/nanorobots for gastrointestinal tract - Ziqi Sui; Chugen Wan; Hefei Cheng; Bin Yang (Frontiers in Chemistry)
The application of micro/nanomotors (MNMs) in the gastrointestinal tract has become a Frontier in the treatment of gastrointestinal diseases. These miniature robots can enter the gastrointestinal tract through oral administration, achieving precise drug delivery and therapy. They can traverse mucosal layers and tissue barriers, directly targeting tumors or other lesion sites, thereby enhancing the bioavailability and therapeutic effects of drugs. Through the application of nanotechnology, these MNMs are able to accomplish targeted medication release, regulating drug release in response to either external stimuli or the local biological milieu. This results in reduced side effects and increased therapeutic efficacy. This review summarizes the primary classifications and power sources of current MNMs, as well as their applications in the gastrointestinal tract, providing inspiration and direction for the treatment of gastrointestinal diseases with MNMs.